(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article provides information about the artistic world of the Korean writer Park Kyong Ni. In the work of Park Kyong Ni, the image of the female psyche and its realization is expressed. Prose works of the artist are analyzed and reactions are expressed. In the works, special emphasis is placed on the characteristics, qualities, and role of a woman in social life.